2020
DOI: 10.1242/dev.178582
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Notch signaling controls the early thymic epithelial progenitor cell state and emergence of the medullary epithelial lineage in fetal thymus development

Abstract: Thymus function depends on the epithelial compartment of the thymic stroma. Cortical thymic epithelial cells (cTECs) regulate T cell lineage commitment and positive selection, while medullary (m) TECs impose central tolerance on the T cell repertoire. During thymus organogenesis, these functionally distinct sub-lineages are thought to arise from a common thymic epithelial progenitor cell (TEPC). However, the mechanisms controlling cTEC and mTEC production from the common TEPC are not understood. Here, we show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 89 publications
(127 reference statements)
12
48
0
Order By: Relevance
“…Constitutive KO Deficiency in p63 resulted in thymic hyploplasia during embryonic development 91,92 Pou2f3 Constitutive KO Pou2f3 deficiency resulted in loss of thymic tuft cells 32,33 RBPJ Cre-Foxn1 Rbpj fl/fl , CreER-Foxa2 Notch fl/fl , Cre-Foxn1 Rosa N1−IC , RBPJ fl/fl Cre-Foxn1; Rosa rtTA ; Tet on -RBPJ-HA Deficiency of either Notch1 or RBPJ inhibited the establishment of mTEC progenitor cells during fetal development, and reduced the mTEC compartment postnatally 179,180…”
Section: Constitutive Expression Of Mutated Nik (G855r)mentioning
confidence: 99%
“…Constitutive KO Deficiency in p63 resulted in thymic hyploplasia during embryonic development 91,92 Pou2f3 Constitutive KO Pou2f3 deficiency resulted in loss of thymic tuft cells 32,33 RBPJ Cre-Foxn1 Rbpj fl/fl , CreER-Foxa2 Notch fl/fl , Cre-Foxn1 Rosa N1−IC , RBPJ fl/fl Cre-Foxn1; Rosa rtTA ; Tet on -RBPJ-HA Deficiency of either Notch1 or RBPJ inhibited the establishment of mTEC progenitor cells during fetal development, and reduced the mTEC compartment postnatally 179,180…”
Section: Constitutive Expression Of Mutated Nik (G855r)mentioning
confidence: 99%
“…Similarly, loss of Notch signaling functions resulted in mTECs hypoplasia. However, the maturation of TEC progenitors whose Notch signaling was defected would be inhibited after Notch signaling function was restored [ 10 ]. Goldfarb et al confirmed that decreasing Notch signaling was required in the later stages of mTECs differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Both the increase in sex steroids and the decrease of growth hormones induce thymic involution with aging [ 9 ]. Several signaling pathways, including Notch signaling [ 10 ], Wnt/β-catenin [ 11 ], and bone morphogenetic protein (BMP) signaling [ 12 ], are also involved in thymic development. Notch signaling plays critical roles in cell development, homeostasis, and disease processes, such as stem cell renewal, embryonic and organic development, cardiomyopathy, oncogenesis, etc [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we focus on the signaling pathway on mTECs maturation. Firstly, the activation of the Notch signaling pathway is indispensable for the specification of the earliest mTECs lineage [ 20 ]. The deletion of Notch1 in TECs during the embryonic period contributes to the depletion of mTEPCs and a significant loss of mTECs [ 21 ].…”
Section: The Development and Differentiation Of Tecs And Epigenetic Mechanismsmentioning
confidence: 99%